Analysis of gene expression in patients during acute cerebral insufficiency and late reconvalescence after severe neuroinfection - A. A. Igolkina; А. V. Kusakin; N. V. Skripchenko; A. A. Vil'nic; L. A. Alekseeva; T. V. Bessonova; O. V. Goleva; N. V. Marchenko; M. A. Irikova; A. B. Chuhlovin; A. V. Krylov; E. V. Baziian; et al. (LLC "Diagnostics and Vaccines", 2024)
Goal. To analyze gene expression in patients with cerebral insufficiency during the critical period and during late convalescence after severe neuroinfection. Materials and methods. The study involved patients with infectious diseases aged from 3 to 17 years, admitted for treatment to the department of resuscitation and intensive care of the Federal State Budgetary Institution DNACIB FMBA of Russia. Whole blood samples were collected before the start of therapy - «Acute period» and during the period of late convalescence after the disease (9, 12, 13 months). RNA sequencing was performed to analyze differential gene expression. Results. Statistically significant differences in expression in the comparison group «Acute period» and «Late convalescence» were detected in 14 genes. Thus, in the «Acute period» group, 12 genes with decreased expression and 2 genes with increased expression were identified: ANGPTL2, encoding angiopoietin-like protein 2 and PCK1 of the phosphoenolpyruvate carboxykinase enzyme. Of the 14 genes, 5 had unknown functions and unidentified orthologues. Conclusion. The authors suggest that increased expression of the ANGPTL2 gene may be the cause of the consequences of hypoxia, which leads to acute cerebral failure during a severe infectious process. Increased expression of PCK1 may indicate increased brain glucose demand during recovery.